Coronary Artery Stenosis Quantification for Computed Tomography Angiography Based on Modified Student's t‐Mixture Model. Issue 5 (11th October 2017) - Sun, Qiaoyu; Yang, Guanyu; Shu, Huazhong; Shi, Daming
Abstract : Coronary artery disease (CAD) is a major cause of death in the world. As a non‐invasive imaging modality, computed tomography angiography (CTA) is now usually used in clinical practice for CAD diagnosis. Precise quantification of coronary stenosis is of great interest for diagnosis and treatment planning. In this paper, a novel cluster method based on a Modified Student's t‐Mixture Model is applied to separate the region of vessel lumen from other tissues. Then, the area of the vessel lumen in each slice is computed and the estimated value of it is fitted with a curve. Finally, the location and the level of the most stenoses are captured by comparing the calculated and fitted areas of the vessel. The proposed method has been applied to 17 clinical CTA datasets and the results have been compared with reference standard degrees of stenosis defined by an expert. The results of the experiment indicate that the proposed method can accurately quantify the stenosis of the coronary artery in CTA.